The question of the question: impactful implementation science to address the HIV epidemic - Geng, Elvin H.; Nash, Denis; Phanuphak, Nittaya; Green, Kimberly; Solomon, Sunil; Grimsrud, Anna; Sohn, Annette H.; Mayer, Kenneth H.; Bärnighausen, Till; Bekker, Linda-Gail (Journal of the International AIDS Society, 2022)
Introduction Questions about the implementation of evidence-based intervention to treat and prevent HIV have risen to the top of the field's scientific priorities. Despite the availability of highly efficacious treatment and prevention interventions, impact has fallen short of targets because these interventions are used with insufficient reach, consistency, sustainability and equity in diverse real-world settings. At present, substantial excitement for implementation science — defined as research methods and strategies to improve use of evidence-based interventions — has focused on developing and disseminating methods to conduct rigorous research. Yet, impactful answers depend on a sometimes less visible, but even more important, step: asking good questions about implementation. Discussion In this commentary, we offer several considerations for researchers formulating implementation research questions based on several distinctive features of the field. First, as findings are used not only by other researchers but by implementers, scientific questions must incorporate a range of stakeholder and community perspectives to be most relevant. Second, real-world settings are contextually diverse, and the most relevant scientific questions must position answers to make sense within these contexts (whether geographical, organizational and sociological), rather than apart from them. Third, implementation is complex and dynamic; consequently, research questions must make use of emerging standards in describing implementation strategies and their effects whenever possible. Finally, the field of implementation science continues to evolve, so framing problems with a diverse disciplinary lens will enable researchers to pose insightful and impactful questions. Conclusions We are now at a juncture marked by both rich evidence-based interventions and a persistent global pandemic. To achieve continued scientific progress against the HIV epidemic, asking the right questions might be part of the answer itself.
Gesehen am 02.07.2022